Microbial translocation, the innate cytokine response, and HIV-1 disease progression in Africa - Redd, Andrew D.; Dabitao, Djeneba; Bream, Jay H.; Charvat, Blake; Laeyendecker, Oliver; Kiwanuka, Noah; Lutalo, Tom; Kigozi, Godfrey; Tobian, Aaron A. R.; Gamiel, Jordyn; Neal, Jessica D.; Oliver, Amy E.; et al. (National Academy of Sciences, 2009)
Reports from the United States have demonstrated that elevated markers of microbial translocation from the gut may be found in chronic and advanced HIV-1 infection and are associated with an increase in immune activation. However, this phenomenon’s role in HIV-1 disease in Africa is unknown. This study examined the longitudinal relationship between microbial translocation and circulating inflammatory cytokine responses in a cohort of people with varying rates of HIV-1 disease progression in Rakai, Uganda. Multiple markers for microbial translocation (lipopolysaccharide, endotoxin antibody, and sCD14) did not change significantly during HIV-1 disease progression. Moreover, circulating immunoreactive cytokine levels either decreased or remained virtually unchanged throughout disease progression. These data suggest that microbial translocation and its subsequent inflammatory immune response do not have a causal relationship with HIV-1 disease progression in Africa.
Keywords: HIV; microbial translocation